An Analysis of Intertemporal Pricing for Forward Foreign Exchange Contracts - HUANG, ROGER D. (Journal of Finance, 1989)
ABSTRACT An asset‐pricing model with an unobservable time‐varying risk premium is used to price forward foreign exchange contracts. Specifically, the term spectrum of forward foreign exchange contracts is examined in order to focus on country‐specific and maturity‐specific information. The testable restrictions imposed by the model are consistent with both cross‐country and cross‐maturity forward contracts except at the short end of the maturity spectrum for cross‐country forward exchange rates. This indicates that the intertemporal model is relatively robust in valuing forward contracts of different maturities and for different exchange rates but that it may fail when there are significant short‐term country‐specific shocks.